2018
DOI: 10.2196/jmir.8947
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in and the Relationships Between Social Anxiety and Problematic Internet Use: Canonical Analysis

Abstract: BackgroundThe cognitive-behavioral model of problematic Internet use (PIU) proposes that psychological well-being is associated with specific thoughts and behaviors on the Internet. Hence, there is growing concern that PIU is associated with psychological impairments.ObjectiveGiven the proposal of gender schema theory and social role theory, men and women are predisposed to experience social anxiety and engage in Internet use differently. Thus, an investigation of gender differences in these areas is warranted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
(56 reference statements)
5
17
0
4
Order By: Relevance
“…Future research is being planned that actually applies the findings of this study and implements the SOMS to investigate health-related outcomes. Future research should also include further investigation of the difference in perception between genders regarding the acceptance of the app, since the possibility of a difference has been suggested in previous research (34).…”
Section: Discussionmentioning
confidence: 95%
“…Future research is being planned that actually applies the findings of this study and implements the SOMS to investigate health-related outcomes. Future research should also include further investigation of the difference in perception between genders regarding the acceptance of the app, since the possibility of a difference has been suggested in previous research (34).…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have reported that negative events impacting on sleep quality mainly included bad dormitory conditions (e.g., noisy roommates, snoring, gaming, lighting, mosquitos), interpersonal conflict, academic pressure, freshmen maladjustment, as well as romantic relationship problems) ( 102 , 103 ). Due to specific characteristics of smartphones (e.g., the many different types of applications), smartphones can be considered as tools that provide self-comfort and satisfy basic need of communication with others in a timely way (i.e., individuals, especially females prefer texting, blogging and chatting via smartphone) ( 104 106 ). Consequently, all kinds of messages from Chinese SNSs such as WeChat and QQ (e.g., different groups comprising class, grade, students’ union, different courses, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Baloǧlu et al . suggest that as levels of social anxiety increase and people spend less time in real‐life relationships and more time on the Internet, their risk of developing PIU becomes greater . Many studies have shown a relation between PIU and ADHD .…”
Section: Discussionmentioning
confidence: 99%
“…51 Baloǧlu et al suggest that as levels of social anxiety increase and people spend less time in real-life relationships and more time on the Internet, their risk of developing PIU becomes greater. 52 Many studies have shown a relation between PIU and ADHD. [53][54][55] Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance-related dependence and gambling dependence.…”
Section: Discussionmentioning
confidence: 99%